The Relationship Between Self-Efficacy and Entrepreneurial Attitudes of Bread and Cake Making Training Participants at BLK Batusangkar - Putriyana, Intan; Solfema, Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research was motivated by the low entrepreneurial attitude of bread and cake making training participants at the Batusangkar BLK, which is believed to be driven by low self-efficacy, served as the impetus for this study. The objectives of this study are to: describe the self-efficacy of participants in the bread and cake making training at BLK Batusangkar, describe the entrepreneurial attitudes of participants in the training at Batusangkar BLK and examine the relationship between the participants self-efficacy and their entrepreneurial attitudes and the cake at BLK Batusangkar. This study employs a quantitative, correlational method. 48 trainees in phases II, III, and V of the bread and cake baking program at BLK Batusangkar in 2022–2023 made up the study's population. Using stratified random sampling, the sample method included 32 individuals, or 67% of the population. A list of assertions is used as a data gathering instrument together with a questionnaire in this data collection technique. Product moment and percentage calculations are used in data analysis techniques. The results of the research show that: 1) The self-efficacy of bread and cake making training participants at BLK Batusangkar is in the low category, 2) The entrepreneurial attitude of bread and cake making training participants at Batusangkar BLK is in the low category, 3) There is a significant relationship between self-efficacy with an entrepreneurial attitude, bread and cake making training participants at BLK Batusangkar.